2016
DOI: 10.1159/000444809
|View full text |Cite
|
Sign up to set email alerts
|

Blood Brain Barrier Disruption in Diabetic Stroke Related to Unfavorable Outcome

Abstract: Background: Diabetes mellitus (DM) is associated with a wide range of microvascular abnormalities in the brain. These include the dysfunction of the blood brain barrier (BBB). In this study, we test the hypotheses that disruption of the BBB in patients presenting with acute stroke is common in patients with DM and is related to outcome. Methods: Sixty-two consecutive patients with ischemic stroke in the middle cerebral artery territory were enrolled within 3-7 days after onset. In ischemic lesion, BBB disrupti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…As a multi-faceted metabolic syndrome, DM has detrimental effects on microvasculature. Prolonged hyperglycemia facilitates the pathophysiology and development of various PNS and CNS disorders 36 . In the co-culture system of HBMEC with human astrocytes, hyperglycemia induced exacerbation of barrier dysfunction was shown to be present as seen by a decrease of transendothelial electrical resistance and increase of EB extravasation 37 .…”
Section: Discussionmentioning
confidence: 99%
“…As a multi-faceted metabolic syndrome, DM has detrimental effects on microvasculature. Prolonged hyperglycemia facilitates the pathophysiology and development of various PNS and CNS disorders 36 . In the co-culture system of HBMEC with human astrocytes, hyperglycemia induced exacerbation of barrier dysfunction was shown to be present as seen by a decrease of transendothelial electrical resistance and increase of EB extravasation 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Structural and functional impairment of the BBB, characterized by disruption of endothelial cell-associated connections, is one of the hallmarks of neurologic disease (36), whereas the severity of BBB disruption has been shown to correlate positively with the severity of IS (37)(38)(39). Our study also found that anti-IL-9 mAb improves the destruction of the BBB after stroke and that its mechanism is related to active repair of the damaged TJPs in brain tissue, which is different from the effects of anti-IL-9 mAb on inflammatory diseases of the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that an up-regulation of MMP-9 activity contributes to the exacerbation of vascular damage in diabetic patients, but not in patients with acute hyperglycemia [ 29 ]. This vascular damage disrupted the blood-brain barrier and led to an unfavourable outcome in diabetic patients [ 30 ].…”
Section: Discussionmentioning
confidence: 99%